Pengaruh Informasi Sistem Penghitungan Nasional Online pada Hasil Pemilu 2019 terhadap Kepercayaan Publik Kota Medan - Febrin Dwi Gloria Tampubolon; Muryanto Amin; Hendra Harahap (PERSPEKTIF, 2021)
The election organizer is obliged to implement every principle in the election. The online National Counting System (Situng) is one of a series of election organizer activities in fulfilling the principle of openness to the public. Improving the quality of service in the General Election aims to increase public trust in the implementation of elections. According to Nunkoo, the principles of transparency and knowledge must be possessed by activity organizers in an effort to increase public trust. Research with this quantitative method looks at how much influence the online national counting system (situng) information (study of the 2019 Election results) has with a study on the people of Medan City. The findings in this study indicate that the process of transparency and increasing knowledge of the people of Medan City has significantly shaped Public Trust in the 2019 Election. The act of transparency has a bigger effect than increasing knowledge of online counting. Given the large role of transparency in shaping public trust in Medan City, this activity needs to be further enhanced to provide a better understanding to the public. And it does not rule out that online situng can increase public knowledge in the electoral field. Situng online is also expected to be an extension of the General Election Commission (KPU) in increasing public knowledge as a basis for experience in the election.